A Case of Massive Pulmonary Embolism with Cardiac Arrest Treated with life-saving Emergency Thrombosis despite Recent Major spinal Surgery: Dealing Acute Right Ventricular Failure through Passive Leg Raising Test (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 62-66 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13564